Turning with Linear Tangential Tool Shift and Its Results - Vasilko, Karol (Manufacturing Technology Journal, 2019)
Machining, mainly turning, si characterised by the highest labour input among the technological methods. This leads to the conditin when, for instance, in line production at hammering power press, which produces forginngs in the stroke of 1 second, tens of lathes follow and their gradual turning with the stroke of tens of seconds up to minutes. Whole history of material machining has been lead with the effort to shorten machining time by the improvement of cutting materials, tool geometry, integration of machining of several workpiece areas in one stroke, etc. The article analyzes an effectiv way to signaficantly sorten machine time, based on the application of turning with tangential tool feed versus workpiece. Inaddition, the method integrates roughing and finishing into one operation and ensures high quality of machined workpiece surface.
Keywords: turning; machining time; tangetial shift; quality of machined surface